Dust ion-acoustic nonlinear wave structures under conditions of near-earth and laboratory plasmas - Popel, S.I. (Вопросы атомной науки и техники, 2012)
A review on dust ion-acoustic nonlinear wave structures in dusty plasmas is presented. The basic experiments on the nonlinear wave structures in dusty plasmas are considered and the corresponding theoretical descriptions are given. A possibility of the existence of the dust ion-acoustic nonlinear structures under near-Earth and space conditions is discussed.